The Incorporation of Creativity in English Writing Materials of Seventh Graders - Felicia Azzahra Kusdinar; Ratna Dewanti; Ilza Mayuni; Dieni Nurhasanah Dwihastuti (Lingua Cultura, 2023)
The research aimed to investigate the incorporation of creativity in writing materials for seventh graders. To achieve quality education for junior high school, teachers and school leaders must provide effective learning materials focusing on curriculum objectives and students’ skills. Besides, creativity was a skill in Profil Pelajar Pancasila that must be implemented in every learning subject. The research applied a qualitative method. Therefore, the respondents were teachers in four junior high schools from Jakarta, Bogor, Depok, Tangerang, and Bekasi area, especially Bogor, Depok, and Bekasi. In-depth interviews were gathered to explore the information on learning materials used by teachers. Moreover, it was also to explore the type of creativity taught through writing materials. The result shows creativity in learning materials lay in phase while-writing. Then, descriptive text is the most genre to support students' creativity, especially on topics of family, friends, personal information, and neighborhood. Therefore, future design of creativity-incorporated writing materials needs to be carried out supporting other phases of writing using updated learning media.